Analysis of performance of classification of Forward-Scattering Radar (FSR) in a cluttered environment: article / Muhammad Najmi Afiq Yahya - Yahya, Muhammad Najmi Afiq (2014)
The effect of clutter to the radar data dispersion has been analysed in this paper. The presence of clutter from the environment may cause errors in the target detection and classification in forward scattering radar (FSR). An experimental approach by comparing the differences between dispersion of the features extraction from the cluttered environment via simulation such as MATLAB can determine the classification of the signal in a database. The outcome from the project should enhance the classification of target classification in a database.